2012
DOI: 10.2165/11589440-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor Use and Medical Costs after Initial Adjuvant Chemotherapy in Older Patients with Early-Stage Breast Cancer

Abstract: Direct medical costs after initial chemotherapy were not statistically different between those receiving G-CSF primary prophylaxis and those receiving no G-CSF, after adjusting for potential confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The limitations of conventional approaches such as excluding those who are censored, or simply ignoring the fact that some patients are censored, are well-documented, and several approaches to estimating population means costs in the presence of censoring have been proposed in the past 15 years [1][2][3][4][5][6][7][8][9][10] and recently compared [7]. Direct comparison of the costs of alternative interventions in observational data requires adjustment for confounding, and previously we have used IPW, partitioned least squares regression to examine adjusted associations between supportive care in breast cancer and the long-term costs of care [11]. To evaluate the performance of IPW for estimating population costs under censoring, we designed an experiment in which we introduced simulated censoring into a cohort of patients all of whom died during the period defined by the data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of conventional approaches such as excluding those who are censored, or simply ignoring the fact that some patients are censored, are well-documented, and several approaches to estimating population means costs in the presence of censoring have been proposed in the past 15 years [1][2][3][4][5][6][7][8][9][10] and recently compared [7]. Direct comparison of the costs of alternative interventions in observational data requires adjustment for confounding, and previously we have used IPW, partitioned least squares regression to examine adjusted associations between supportive care in breast cancer and the long-term costs of care [11]. To evaluate the performance of IPW for estimating population costs under censoring, we designed an experiment in which we introduced simulated censoring into a cohort of patients all of whom died during the period defined by the data.…”
Section: Resultsmentioning
confidence: 99%
“…IPW has proved to be the more general approach and has been adopted and refined in subsequent publications by other researchers [10]. Recently, we used partitioned, IPW, least squares regression to estimate the long-term incremental costs associated with using granulocyte colony-stimulating factor to support initial adjuvant chemotherapy for early-stage breast cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…These findings is supported by the study done by Lee et al , in which they found that NHL patients who received primary prophylactic G‐CSF had significantly fewer FN compared with those who did not, with only a small increase in direct financial cost. However, whether primary prophylactic G‐CSF is cost‐effective among patients with breast cancer is still controversial in previous studies . These conflicts could be due to different costs of medical services in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although many clinical trials have demonstrated the beneficial effect of prophylactic use of G-CSF in decreasing incidence of FN and infection, there have been conflicting data regarding its economic impacts [4][5][6][7][8][9][10][11][12]. Some studies even suggest that primary G-CSF did not result in cost savings [13] or could only be considered cost-effective under certain situations such as a higher willingness-to-pay [12].…”
Section: Introductionmentioning
confidence: 99%
“…All paid amounts were inflated to 2009 US dollars based on the hospital input price index for part A claims and the medical expenditure index for part B claims [38]. Since SEER-Medicare data are limited in time, our approach to estimating population mean costs accounted for censoring in the data using inverse probability weighting (IPW) [3945]. …”
Section: Methodsmentioning
confidence: 99%